Impact of social media marketing on the performance of online shopping in nairobi, kenya - NDATHI, JOSEPH NJUKI (UoEm, 2024)
Technological advancements have brought about new social media related to the internet. The internet which is currently a perfect tool of socialization around the world have a greater impact on how the businesses are carried out globally. Social media generally provides a perfect market for businesses especially the current online businesses. The social media allows customers and prospects to communicate directly to the business. This paper aims to address the question of how social media marketing impacts online businesses based on a study regarding how these social media interactions impact online sales, purchases as well as its impacts on customers’ behavior toward a business as a brand. The research used secondary data sources. Sources included existing studies, business journals and also latest reports on uses of social media. The information in this study requires additional information since there is no enough existing studies on social media. Theoritical literature mostly covers studies of how social media has affected retail business with activities related to online retail businesses with assumptions customers’ purchasing behavior is influenced the same by social media. Social media is evolving rapidly and therefore it requires continuous assessment for businesses to be at par with developing technology. Social media marketing has overturned the known traditional marketing methods. With many businesses going online, it is therefore important businesses to understand usage of social media for marketing.